The Effect of Using Safety Headgears in Taekwondo on Dynamic Parameters Related to Head Injury - Neda Boroushak; Hasan Khoshnoodi; Mansour Eslami; Hossien Khodarahmi (Vesnu Publications, 2018)
Introduction: The influence of using safety headgears on important parameters of head injury in taekwondo has not been specified yet. The aim of this study was to investigate the amount of changes in rotational acceleration, linear acceleration, and impact force of head by using headgears in taekwondo. Materials and Methods: In this experimental study, 14 elite men taekwondo athletes participated. To investigate the effect of headgears on head injury parameters, a machine was used that consisted of an artificial neck and head, a mechanical arm that represented the taekwondo athlete foot, and a computer system for monitoring, supervisioning and recording the data, that was made by the researcher. The results were obtained in the MATLAB program. One-way repeated measures ANOVA and Bonferroni tests were applied to analyze the statistics results (P < 0.050). Results: All headgears significantly reduced the impact force and linear acceleration of the head (P = 0.001). Foreign headgears and Iranian headgears significantly decreased and increased rotational acceleration, respectively (P = 0.001). Conclusion: All headgears are good protectors for preventing injuries due to impact force and linear acceleration. But, none of these headgears could reduce rotational acceleration to less than the threshold of head injury.